Causes of Glacier Melt Extremes in the Alps Since 1949. Issue 2 (30th January 2018) - Thibert, E.; Dkengne Sielenou, P.; Vionnet, V.; Eckert, N.; Vincent, C.
Abstract: Recent record‐breaking glacier melt values are attributable to peculiar extreme events and long‐term warming trends that shift averages upward. Analyzing one of the world's longest mass balance series with extreme value statistics, we show that detrending melt anomalies makes it possible to disentangle these effects, leading to a fairer evaluation of the return period of melt extreme values such as 2003, and to characterize them by a more realistic bounded behavior. Using surface energy balance simulations, we show that three independent drivers control melt: global radiation, latent heat, and the amount of snow at the beginning of the melting season. Extremes are governed by large deviations in global radiation combined with sensible heat. Long‐term trends are driven by the lengthening of melt duration due to earlier and longer‐lasting melting of ice along with melt intensification caused by trends in long‐wave irradiance and latent heat due to higher air moisture. Key Points: Glacier melt follows extreme value statistics if nonstationarity is accounted for Global radiation, the latent heat flux, and the amount of snow at the beginning of the melting season are three independent controls of melt variability Extremes are ruled by large deviations in global radiation combined with sensible heat; long‐wave irradiance and latent heat flux are involved in long‐term trends